Multiple metastatic deposits in hepatocellular carcinoma: Hunt for diagnosis of primary malignancy - Satish Arakeri; Anjali Sharma (Wolters Kluwer Medknow Publications, 2023)
Hepatocellular carcinoma (HCC) is the most common primary tumor of the liver. An elderly male patient presented with pain over the right upper abdomen. Hepatomegaly was noted with a firm to hard in consistency. Ultrasonography shows a large irregular nodule in the liver measuring 6 cm × 5 cm with increased echogenicity and increased vascularity. Computed tomography thorax shows 8 cm × 5 cm lytic lesion with soft tissue density in the right posterior chest wall with expansion and erosion of the third, fourth, and fifth rib lesions. Tru-cut biopsy from lung mass as well as the liver mass has been taken. The final diagnosis of HCC was made. HCC is a highly malignant tumor of the liver. It is usually asymptomatic. However, it presents as right upper quadrant pain, palpable mass, and weight loss. Most cases have underlying liver disease. Accurate diagnosis of HCC with metastatic deposits is very important in defining the management of the primary malignancy.